Altered intrinsic brain functional connectivity in drug-naïve Parkinson's disease patients with LRRK2 mutations. (14th May 2018) - Hou, Yanbing; Luo, Chunyan; Yang, Jing; Ou, Ruwei; Song, Wei; Chen, Yongping; Gong, Qiyong; Shang, Huifang
Highlights: There are differences of FC between PD patients with and without LRRK2 mutation. The FC of superior frontal gyri decreased with age in the mutation carriers. Both subgroups showed a consistent alteration within some striatal circuits. Our results are preliminary and further investigations are needed. Abstract: Background: Leucine-rich repeat kinase 2 ( LRRK2 ) has been recently identified as a causative gene of Parkinson's disease (PD), and the LRRK2 R1628P and G2385R mutations are common in ethnic Han-Chinese PD patients. However, the pathogenic mechanism of LRRK2 mutations in PD remains largely unknown. Methods: Resting-state functional MRI (fMRI) was used to assess the functional connectivity (FC) of the striatal subregions of 11 ethnic Han-Chinese drug-naïve PD patients with the LRRK2 R1628P or G2385R mutations, 11 ethnic Han-Chinese drug-naïve PD patients without such mutations, and 22 healthy control (HC) subjects. Results: Compared with the HC subjects, both subgroups of the PD patients showed alterations in the FC within the sensorimotor-striatal and posterior putamen-striatal circuits. In addition, relative to the subgroup of PD patients without the LRRK2 mutations, the subgroup of PD patients with the LRRK2 mutation exhibited decreased FC between the putamen and the bilateral superior frontal gyri, precuneus and calcarine gyri. The FC between the putamen and the bilateral superior frontal gyri decreased with age in the LRRK2 mutation carriers but not in the non-carriers. Conclusion: Differences in the FC between ethnic Han-Chinese drug-naïve PD patients with and without the LRRK2 mutation may provide new insights into the understanding of the neural functional changes in ethnic Han-Chinese PD patients with LRRK2 mutations. However, our results are preliminary, and further investigations are needed.